Economic and Socio-demographic Factors That Affect Takaful Demand in Malaysia - Zahirah Nordin; Sharifah Fairuz Syed Mohamad; Syed Aun Raza Rizvi (Semarak Ilmu Publishing, 2024)
Non-Indexed Publication